2013
DOI: 10.1007/s10763-013-9430-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cognitive Styles on Naïve Impetus Theory Application Degrees of Pre-Service Science Teachers

Abstract: The purpose of this study was to determine whether there is a relationship between pre-service science teachers' Field Dependent or Field Independent (FD/FI) cognitive styles and the application of degrees of naive impetus theory. The sample consisted of 122 pre-service science teachers (97 females and 25 males) who were enrolled in the Introductory Physics course required by the Science Education program. Data were collected in two successive years, after the completion of the required Introductory Physics un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…The findings obtained from this study showed that students with fieldindependent cognitive style were significantly more successful than the students with field-dependent cognitive style statistically in terms of scores obtained from both Life Based Concept Test and Force Concept Map. When the findings of the related literature are examined, it is seen that the students with field-independent cognitive style in science have a higher level of achievement in terms of conceptual understanding and achievement than the field-dependent students (Al-Naeme, 1991;Altiparmak, 2009;Ates & Cataloglu, 2007;Ates & Karacam, 2005;Cataloglu & Ates, 2013;Crow & Piper,1983;Celik, 2010;Ozarslan & Bilgin, 2016;Prayekti, 2015;Stamovlasis, Tsitsipis & Papageorgiou, 2009;Ziane, 1996).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The findings obtained from this study showed that students with fieldindependent cognitive style were significantly more successful than the students with field-dependent cognitive style statistically in terms of scores obtained from both Life Based Concept Test and Force Concept Map. When the findings of the related literature are examined, it is seen that the students with field-independent cognitive style in science have a higher level of achievement in terms of conceptual understanding and achievement than the field-dependent students (Al-Naeme, 1991;Altiparmak, 2009;Ates & Cataloglu, 2007;Ates & Karacam, 2005;Cataloglu & Ates, 2013;Crow & Piper,1983;Celik, 2010;Ozarslan & Bilgin, 2016;Prayekti, 2015;Stamovlasis, Tsitsipis & Papageorgiou, 2009;Ziane, 1996).…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Each student's cognitive style is different; therefore, learning must facilitate all types of student cognitive styles (Krisdiantoro & Prihatnani, 2019). Students' cognitive styles' differences are significantly correlated with problem-solving, students' learning outcomes, and mathematics appreciation (Cataloglu & Ates, 2014;Klaczynski, 1994;Marlissa & Widjajanti, 2015;Tinajero & Páramo, 1998).…”
Section: Cognitive Styles and Problem-solvingmentioning
confidence: 99%
“…That's why it is probable to obtain different results in the process of investigating these people having different cognitive characteristics. As a matter of fact, it appears in conducted studies that field dependent and independent people reveal different results in terms of investigated variable [3,4,5,8,26].…”
Section: Cognitive Stylesmentioning
confidence: 99%